Sprouting characteristics and associated changes in nutritional composition of cowpea (Vigna unguiculata) - Devi, Chingakham Basanti (J Food Sci Technol, 2015)
Cowpea (Vigna unguiculata), is an important arid legume with a good source of energy, protein, vitamins, minerals and dietary fibre. Sprouting of legumes enhances the bioavailability and digestibility of nutrients and therefore plays an important role in human nutrition. Improved varieties of grain cowpea viz. Pant Lobia-1 (PL-1) and Pant Lobia-2 (PL-2) and Pant Lobia-3 (PL-3) were examined for sprouting characteristics and associated changes in nutritional quality. Soaking time, sprouting time and sprouting temperature combinations for desirable sprout length of ¼ to ½ inch for cowpea seed samples were standardized. All the observations were taken in triplicate except soaking time, where six observations were taken in a completely randomized design of three treatments. Results revealed that optimum soaking time of PL-1 and PL-2 seed was 3 h whereas PL-3 required 9 h. Sprouting period of 24 h at 25 °C was found to be desirable for obtaining good sprouts. Significant improvement in nutritional quality was observed after sprouting at 25 °C for 24 h; protein increased by 9–12 %, vitamin C increased by 4–38 times, phytic acid decreased by 4–16 times, trypsin inhibitor activity decreased by 28–55 % along with an increase of 8–20 % in in-vitro protein digestibility.